Demonstration Method with TPACK Approach to Improve the Writing Ability of Procedure Text in Fourth Grade - Rizka Mulyanah; Farid Rizqi Maulana; Deni Wardana (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This research investigates wheter integrating the demonstration method with a TPACK (Technological Pedagogical Content Knowledge) approach in classroom learning can improve students ability to write procedure texts. A quasi experimental pre-test post-test control group design was employed to examine this effect. The target population for this study included all fourth grade students at SDN Kedaung Wetan 2. A sample of 40 students was selected, with 20 students from class 4A assigned to the control gorup and 20 students from class 4B assigned to the experimental group. The instrument used in this study was a written test. Data analysis was performed using the SPSS 27 program. Both the Paired Sample T-Test (Sig. (2-tailed) = 0.001) and the Independent Samples T-Test (Sig. (2-tailed) = 0.075) yielded statistically significant results (p = 0.05), indicating that the null hypothesis (Ho) can be rejected in favor of the alternative hypothesis (Ha). This suggest a significant difference between the learning outcomes of students receiving traditional instruction. Furthermore, the N-Gain Score analysis revealed an average improvement of 56% in the learning outcomes. This finding supports the notion that the TPACK integrated method has a positive inflluence on students ability to write procedure texts.